TRANSMISI SEKSUAL (PMTS) DI KALANGAN WANITA PEKERJA SEKS (WPS) LOKASI GANG LALER KEMAYORAN JAKARTA PUSAT TAHUN 2014 - Hubaybah -; Fadzlul - (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2016)
Abstract PMTS (HIV-AIDS Prevention Program through Sexual Transmission) is a program of HIV-AIDS prevention which was initiated by the National AIDS Commission (KPAN), its aim is to do HIV prevention comprehensively, interactively and effectively on the key population which is female sex workers, however, as it is known that the purpose of this program has not been reached. The research objective was to evaluate HIV-AIDS prevention program through sexual transmittion among female sex workers at Gang Laler Kemayoran Central Jakarta 2014.The research is using cualitative method, data assessment method is found through deep interview and document review, data validation is using triangulate sourch, data and method. The reseach show thatlack of coordination, lack of funds, facilities and infrastructure have become the reason whythe goal PMTS program cannot be achieved yet, marked with dysfunctional Location Working Unit. Location Working Unit is one key to success that can run the entire activities, so the suggestions of this research are to improve the coordination of KPAK with LSM/NGO, SKPD, Location Working in a form of routine meetings, to allocate the routine funds for Location Working Unit and the entire activities, as well as providing facilities and infrastructure to support the activities.   Keywords: HIV AIDS, PMTS, Program Evaluation